Kekaburan Norma dalam Kebebasan Berekspresi di Era Digital: Analisis Undang-Undang Nomor 1 Tahun 2024 tentang Perubahan Atas Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik - M. Apandi; Karlina Rahayu; Wahyu Agus Prayugo; Lisda Ariany (CV Rewang Rencang, 2024)
This study aims to analyze (1) the vagueness of the norm in Article 27 A concerning defamation affects freedom of expression (2) how the vagueness of the norm in Article 28 Paragraph 1 concerning the spread of fake news impacts freedom of expression in the digital era. This study uses a normative legal method. The object of this study is Law Number 1 of 2024 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions. The results of the study indicate that (1) the vagueness in Article 27 A concerning defamation can lead to violations of the law, because its interpretation is subjective. This can cause fear for individuals or groups to express opinions or criticism in the digital space, because of the threat of unclear sanctions. (2) Article 28 Paragraph 1 which regulates the spread of fake news also shows vagueness in the definition of